Investigation on Seismic Damage Model Test of a High Concrete Gravity Dam Based on Application of FBG Strain Sensor - Mingming Wang; Jianyun Chen; Hai Wei; Bingyue Song; Weirong Xiao (Complexity)
A 203-m-high gravity dam being built in earthquake-prone areas needs to be investigated very carefully to determine its dynamic responses, damage mechanism, and safety evaluation. The dynamic characteristics, seismic responses, failure mode, and safety evaluation of the above structure are presented through dynamic fracture test for small-scale model on shaking table. Because the strength of the model material is very low, the traditional strain gauge is also not easy to be glued to the surface of model. It is difficult to measure the accurate strain data of small-scale model during testing. Therefore, Fiber Bragg Grating (FBG) strain sensor is presented to obtain the strain of small-scale model during testing, due to its high sensitivity. The dynamic strain and residual strain are obtained with the FBG sensors embedded in model. The FBG sensor is adhered to model material completely and shows advantages of ease for installation, high sensitivity, and reliability compared with traditional resistance strain gauge. The model during testing is submitted with earthquake wave from the Chinese Code. In the experiment, the peak ground acceleration (PGA) of the first crack in the model indicates the safety level of the gravity dam. The crack locations and forms determine the damageable part of gravity dam under intense earthquake. After the final analysis, the safety evaluation result of the gravity dam under strong earthquake is given in order to guide the implementation of the project.